О влиянии конфигурации деформируемого уплотнения на тепловое поле в реакционной ячейке при выращивании монокристаллов алмаза методом Т-градиента - Будяк, А.А.; Ивахненко, С.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
In a reaction vessel there was made the calculation of a thermal field to grow single crystals of diamond by a method of the T-gradient for two variants of working space: the first – “ the anvil with recess”, the second – HPA of “toroid” type is applied. It is shown, that in the second case the average temperature in metal- solvent vises up to 80⁰ C, and the average temperature gradient decreases two times as much.